Pop - Wilson, Simon (London : Thames and Hudson, 1974)
Rauschenberg, Robert ; Johns, Jasper ; Lichtenstein, Roy ; Warhol, Andy ; Oldenburg, Claes ; Wessenmann, Tom ; Rosenquist, James ; Indiana, Robert ; Ruscha, Edward ; Hamilton, Richard ; etc.
Engels
boek